Environmental sustainability of forestal concessions in Huanuco department, Peru - Valdivia Espinoza, Luis Alberto; Gonzalez Manrique de Lara, Tito Felipe; Julca-Otiniano, Alberto Marcial (Instituto de Ecología, A.C., 2020)
The sustainable utilization of forest resources consists of using them to generate wealth, improving social indicators and avoiding environmental imbalance. The objective of the study was to determine the environmental sustainability of forest concessions in the Department of Huanuco, Peru, through a multicriteria analysis based on the use of indicators. Indicators were built including the diversity of edaphic macro-fauna evaluated down to 30 cm deep, as evidence of soil conservation and maintenance state. The indicators were standardized using a scale from 0 to 4.0, 4.0 being the highest value of sustainability; they were subsequently weighted by multiplying the scale by a coefficient, based on their importance with respect to sustainability. A forest concession is environmentally sustainable, if the Environmental Sustainability Index (ESI) is ≥ 2.0. The designed survey was applied to stakeholders and workers of forestal concessions. To know if the ESI in 60% of forest concessions exceeds the value 2.0, the Chi Square test was used; Pearson’s correlation was also performed between indicators, with 95% reliability. The Chi Square test confirms that forest concessions with manual forestal utilization (60% of the total) are environmentally sustainable (X2 = 0.056, p-value = 0.814). A strong statistically significant positive correlation was recorded (r = 0.970, p-value < 0.05) between "conservation and maintenance of soil resource" (CMSR) and "conservation of wild flora" (CWFl) indicators. Manual forest utilization maintains harmony with the natural environment, and even when mechanized forestal is utilized with a reduced impact, it generates damage to the ecosystem.